2018
DOI: 10.1002/smll.201800394
|View full text |Cite
|
Sign up to set email alerts
|

A Polypyrrole Elastomer Based on Confined Polymerization in a Host Polymer Network for Highly Stretchable Temperature and Strain Sensors

Abstract: For the purpose of stretchable electronics, broad interests have been paid to elastic conductors by which high tensile strain over 100% can be readily achieved. Here, a scalable-processing, dyeing-like strategy for highly stretchable polypyrrole elastomer (1450% in strain) is conceived without particular topological design. This approach effectively improves the mechanical properties of the classic insoluble polypyrrole by confined polymerization within an elastic polymer network. In terms of the easy processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Internet of Things (IoT) has been recently evolved by the state‐of‐the‐art piezoresistive nanocomposite strain sensors due to their unusual sensing capabilities, that is, high sensitivity and flexibility at the same time . Such versatile sensors involve a nanoscale percolating conductive network (formed by a conductive filler) elaborated into a nonconductive, flexible polymeric matrix which can be fabricated in the forms of 1D yarns, 2D thin films, or 3D self‐sensing structures . Piezoresistive sensors have shown a great promise in sensing human movements, heart rate monitoring and pulse measurement; they have been used for applications in machine learning (e.g., in soft robotics), as well as real‐time structural health monitoring (SHM) and resin curing screening in the structural parts and composites.…”
Section: Introductionmentioning
confidence: 99%
“…Internet of Things (IoT) has been recently evolved by the state‐of‐the‐art piezoresistive nanocomposite strain sensors due to their unusual sensing capabilities, that is, high sensitivity and flexibility at the same time . Such versatile sensors involve a nanoscale percolating conductive network (formed by a conductive filler) elaborated into a nonconductive, flexible polymeric matrix which can be fabricated in the forms of 1D yarns, 2D thin films, or 3D self‐sensing structures . Piezoresistive sensors have shown a great promise in sensing human movements, heart rate monitoring and pulse measurement; they have been used for applications in machine learning (e.g., in soft robotics), as well as real‐time structural health monitoring (SHM) and resin curing screening in the structural parts and composites.…”
Section: Introductionmentioning
confidence: 99%
“…Components used in the mechanical sensors can be divided into active materials and supporting materials. Metal‐based materials (eg, liquid metals, metal particles, and NWs), carbon‐based materials (eg, carbon black [CB], CNT, and graphene), conductive polymers (eg, PPy, poly(3,4‐ethylene dioxythiophene):poly(styrene sulfonate) [PEDOT:PSS], and hydrogel), and other materials (eg, MOF, MXene) have been used as the active materials.…”
Section: Skin‐inspired Mechanical Sensorsmentioning
confidence: 99%
“…In addition, conductive polymers with better processability and stretchability, have been widely used as active materials for mechanical sensors. For example, He et al reported a highly stretchable conductive network by interpenetrating PPy into polyurethane, which can be used to prepare stretchable electronics with arbitrary shape and size . PEDOT:PSS is another common conductive polymer.…”
Section: Skin‐inspired Mechanical Sensorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Soft electronics refer to those electronic elements and circuits that could retain their functions in the presence of proper deformation under external stress. [10] They have shown great potentials in the applications of soft robotics, [11][12][13][14][15][16][17] health monitoring, [18][19][20][21] and the Internet of Things (IoTs). [22] Taking exercising as an example, soft electronics is envisioned to quantitatively evaluate our physical status and training effect without causing uncomfortable feelings.…”
Section: Soft Electronics Based On Liquid Conductorsmentioning
confidence: 99%